Heart rate variability changes in patients with obstructive sleep apnea: A systematic review and meta‐analysis. (7th September 2022) - Wang, Zuxing; Jiang, Fugui; Xiao, Jun; Chen, Lili; Zhang, Yuan; Li, Jieying; Yi, Yang; Min, Wenjiao; Su, Liuhui; Liu, Xuemei; Zou, Zhili
Summary: Obstructive sleep apnea is a common sleep breathing disorder related to autonomic nervous function disturbances. Heart rate variability is an important non‐invasive indicator of autonomic nervous system function. The PubMed, Embase, Medline and Web of Science databases were systematically searched for English literature comparing patients with obstructive sleep apnea with controls up to May 2021. Heart rate variability outcomes, including integrated indices (parasympathetic function and total variability), time domain indices (the standard deviation of NN intervals and the root mean square of the successive differences between normal heartbeats) and frequency domain indices (high‐frequency, low‐frequency, very‐low‐frequency and the ratio of low‐frequency to high‐frequency) were derived from the studies. Twenty‐two studies that included 2565 patients with obstructive sleep apnea and 1089 healthy controls were included. Compared with controls, patients with obstructive sleep apnea exhibited significantly reduced parasympathetic function. For the obstructive sleep apnea severity subgroup meta‐analysis, patients with severe obstructive sleep apnea had significantly lower parasympathetic function, high‐frequency, root mean square of the successive differences between normal heartbeats and standard deviation of NN intervals, and higher low‐frequency and ratios of low‐frequency to high‐frequency. However, only the ratio of low‐frequency to high‐frequency was significantly higher in patients with moderate obstructive sleep apnea than in controls. Finally, for the collection time analysis, patients with obstructive sleep apnea had significantly higher low‐frequency and ratio of low‐frequency to high‐frequency at night, significantly lower parasympathetic function, high‐frequency, root mean square of the successive differences between normal heartbeats and standard deviation of NN intervals, and a higher ratio of low‐frequency to high‐frequency during the day than controls. Autonomic function impairment was more serious in patients with severe obstructive sleep apnea. During sleep, low‐frequency can well reflect the impairment of autonomic function in obstructive sleep apnea, and the ratio of low‐frequency to high‐frequency may play an important role in obstructive sleep apnea diagnosis.